Harboring alien lifeworlds: the second-person in thought insertion - Garavito, María Clara (Cuadernos de Filosofía Latinoamericana, 2024)
In phenomenology, the delusion of thought insertion is described and explained in different ways. There is a common idea that the delusion depends either on a lack of sense of agency or on a confusion between self and others. I propose that the delusion is an alienation in regard to what is expressed in some thoughts, that make them unfamiliar. In this perspective, the delusion has to do with the fact that the lifeworld expressed in inserted thought is given in a second-person perspective, is rooted in a different lived-body experience than one’s own. This contrasts with ordinary thoughts which are given in the first-person perspective, with which we have a sense of intimacy. This discussion is an opportunity for putting forth the idea of the second-person perspective: that is, certain experiences of the world are given to me through others, as distinct from those that are given to me directly as a lived body. In inserted thoughts, there is a sense in which some perspectives of reality, different to my own, are disclosed through an alien voice or through inside me. The distinction between the first person and second person perspectives leads to a better understanding of the primal constitution of the self and of others, based on the relation between the body and the world as it is given to us.